2013
DOI: 10.1002/ejhf.34
|View full text |Cite
|
Sign up to set email alerts
|

The renal arterial resistance index: a marker of renal function with an independent and incremental role in predicting heart failure progression

Abstract: AimsThe renal arterial resistance index (RRI) is a measure of renal blood flow obtained by Doppler ultrasonography, which has been demonstrated to reflect both vascular and parenchymal renal abnormalities. The aim of the study was to evaluate clinical correlates and the prognostic relevance of RRI in a group of patients affected by chronic heart failure (CHF Methods and resultsWe enrolled 250 CHF outpatients in a stable clinical condition and receiving conventional therapy. Peak systolic velocity and end-dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 34 publications
1
49
0
2
Order By: Relevance
“…In addition to HF1 and HF2, other correlates might help in screening for diastolic LV dysfunction, including albuminuria [40], circulating NTproBNP [5], and the renal resistance index [41]. However, in our participants randomly recruited from a general population the prevalence of albuminuria was too low to be useful as a screening instrument.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to HF1 and HF2, other correlates might help in screening for diastolic LV dysfunction, including albuminuria [40], circulating NTproBNP [5], and the renal resistance index [41]. However, in our participants randomly recruited from a general population the prevalence of albuminuria was too low to be useful as a screening instrument.…”
Section: Discussionmentioning
confidence: 95%
“…A major concern of acute renal artery occlusion is whether an occlusion justifies an intervention since the renal parenchyma might not be salvable. Radiological findings have been proposed for predictors of renal function recovery such as the renal arterial resistance index [10]. Furthermore, reconstitution of a distal renal artery segment, which is supplied by collateral branches, and the presence of a late phase nephrogram on CTA, MRA, or DSA indicate some grade of residual perfusion [11].…”
Section: Discussionmentioning
confidence: 99%
“…Renal arterial Doppler was performed after echocardiographic examination by using the same echograph (Vivid 7; GE Vingmed Ultrasound, General Electric) and the same 4-MHz probe as previously described [7]. Briefly, the course of the right or left kidney segmental arteries were visualized by color flow Doppler, and pulsed Doppler was performed at the middle tract level of the best one visualized.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that it can integrate information obtained from the estimation of the glomerular filtration rate (GFR), thus improving patients' prognosis [3,4,5,6,7]. Moreover, RRI could detect early renal function abnormalities because it has been demonstrated to be associated with both vascular lesions and histological abnormalities [6].…”
Section: Introductionmentioning
confidence: 99%